Isolation and Identification of Phosphate Solubilizing Bacteria (PSB) from the Rhizosphere of Thymus vulgaris L. - Murat GÜLER (ISPEC Journal of Agricultural Sciences)
Phosphate-solubilizing bacteria dissolve insoluble form of phosphate in the soil with different mechanisms, converting them into a form that can be used, and replaced by chemical fertilizers providing beneficial use of a natural reserve. Although research on phosphate solubilizing bacteria has increased recently, research on the thyme rhizosphere is still limited. It is necessary to investigate different rhizospheric local bacteria that can solubilize phosphate and replace chemical fertilizers. 42 bacterial isolates were obtained from the rhizosphere of Thyme (Thymus vulgaris L.) in this study. Among these isolates, 13 phosphate-solubilizing bacterial isolates were selected which formed a transparent (halo) region around the colonies on Pikovskaya’s Agar (PKA) plates. Isolates were identified using the MALDI-TOF MS method. The morphological, biochemical and IAA production of these isolates as well as quantitative measurements of phosphate solubilization of the isolates in NBRIP broth medium was evaluated. The highest efficiency was noted from Bacillus pumilus PCB-6 with solubilization value of 326.8 ppm. This was followed by Acinetobacter calcoaceticus PCB-3 with solubilization value of 313.8 ppm and Pantoeae agglomerans PCB-4 with solubilization value of 307.4 ppm, respectively. Among the Phosphate solubilizing bacterial isolates, P solubilization index was defined as between 1.6 and 4.2 on PKA agar medium. Additionally, the highest IAA production, at 18.43 µg ml-1, was obtained from Pantoeae agglomerans PCB-4. This was followed by Bacillus pumilus PCB-6 with 17.40 µg ml-1 and Acinetobacter calcoaceticus PCB-3 with 16.71 µg ml-1. This study clearly shows that selected local isolates can be used as effective phosphate-based microbial fertilizers.